Pendampingan Peningkatan Potensi Objek Retribusi Daerah Melalui IMB di Distrik Tanah Miring dan Semangga Kabupaten Merauke - Raubaba, Henry Soleman; Alahudin, Muchlis (IGKOJEI: Jurnal Pengabdian Masyarakat, 2020)
ABSTRACT Increasing the potential of regional retribution objects in the Merauke Regency is an effort of the regional government to increase regional budget revenues. Izin Mendirikan Bangunan (IMB) or the "Construction Permit", which is the primary source of the regional retribution in Merauke Regency, is one of the requirements for the people to legally own a building. The dearth of resources at the relevant agencies, combined with the lack of awareness and knowledge within the community in managing the IMB, has caused the implementation of the IMB to run ineffectively. This service aims to survey potential user fees in the Kurik, Tanah Miring, and Semangga Districts of Merauke Regency by registering the ownership of the IMB and understanding the problems that occur in the community related to the management of IMB and at the same time to obtain a constructive input for the Investment Office and One-Stop Integrated Services of Merauke Regency in the framework of increase in IMB retribution in 2020. Keywords: Retribution objects; IMB; Merauke ABSTRAK Peningkatan potensi objek retribusi daerah di Kabupaten Merauke merupakan upaya pemerintah daerah dalam meningkatkan pendapatan anggaran daerah. Izin Mendirikan Bangunan (IMB) sebagai primadona objek retribusi daerah di Kabupaten Merauke merupakan salah satu kebutuhan masyarakat dalam mendapatkan legalitas kepemilikan bangunan gedung. Ketersediaan sumber daya di instansi terkait, kurangnya kesadaran dan pengetahuan masyarakat dalam mengelola IMB menyebabkan implementasi IMB tidak berjalan efektif. Pengabdian ini bertujuan melaksanakan survey potensi retribusi bagi masyarakat di Distrik Tanah Miring dan Distrik Semangga Kabupaten Merauke dengan mendata kepemilikan IMB dan mengetahui permasalahan yang terjadi di masyarakat terkait pengurusan IMB dan sekaligus menjadi masukan bagi Dinas Penanaman Modal dan pelayanan Terpadu Satu Pintu Kabupaten Merauke dalam rangka peningkatan retribusi IMB tahun 2020. Kata Kunci: Objek retribusi; IMB; Merauke